1975
DOI: 10.1021/j100577a006
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of silica supported chromium ions. II. One-ligand complexes. Adsorption of carbon monoxide, carbon dioxide, and pyridine

Abstract: Publication costs assisted by Italian CNR Py, CO2, and CO interaction with reduced diluted silica supported Cr catalysts is presented. Py shows the presence of Lewis acidity on the surface. CO2 only interacts in a linear form with surface Cr ions. CO is the most interesting ligand, as three different kinds of surface ions are observed (Cr111 and two Cr11 species). At high pressures or low temperatures CO also adsorbs in a bridged form thus revealing chromium ions pairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
71
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 0 publications
7
71
0
Order By: Relevance
“…As such, it can be assumed that they are due to CO adsorbed on Pd. [32][33][34][35][36] The same behavior was previously observed with the Pd-W/ Al 2 O 3 catalyst. 25 Additionally, there is a decrease in the probability of having two adjacent Pd atoms binding CO in a bridging manner.…”
Section: Co and No Adsorption Measurementssupporting
confidence: 63%
“…As such, it can be assumed that they are due to CO adsorbed on Pd. [32][33][34][35][36] The same behavior was previously observed with the Pd-W/ Al 2 O 3 catalyst. 25 Additionally, there is a decrease in the probability of having two adjacent Pd atoms binding CO in a bridging manner.…”
Section: Co and No Adsorption Measurementssupporting
confidence: 63%
“…This was in agreement with EPR spectra that showed no Cr signal since Cr ?2 is EPR silent, although it is d4 and paramagnetic in most chemical environments [21]. Chemical probing of the reduced surface sites with CO-IR studies suggested that two surface Cr ?2 and one surface Cr ?3 site may be present after CO reduction [22]. Other studies concluded that even more reduced surface Cr sites may be present [9, 12, 13, 23- Table 1).…”
Section: Activation Of Cro X /Sio 2 Catalysts With Comentioning
confidence: 86%
“…Since the oxidized high-temperature precursor state was described by the dichromate structure, the formation of low-valent Cr ion pairs on the support surface seems to be plausible. On adsorption of CO at a coverage corresponding to a 1: 1 ratio for Cr: CO three carbonyl stretching vibrations at 2191, 2186 and 2181 cm-1 were observed [263], which can be assigned to three types of linear Cr-CO complexes, namely a C~ + -CO complex (2191 cm -1) and two different 0.2+ -CO complexes (2186 and 2181 cm-1 ). At higher coverages (Cr:CO > 1), CO also adsorbs in a bridging form which gives rise to a band at 2095 cm -1.…”
mentioning
confidence: 94%